Association of single nucleotide polymorphism in exon of transient receptor potential melastatin 2 gene with sepsis - Fang, Minbo; Chen, Qixing; Wu, Shuijing; Fang, Xiangming (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2016)
To investigate the association between single nucleotide polymorphism (SNP) in the 11th exon of transient receptor potential melastatin 2 (TRPM2) gene with the susceptibility and outcome of sepsis. A total of 119 septic patients and 112 normal subjects were enrolled from the First Affiliated Hospital, Zhejiang University School of Medicine. Among 119 septic patients, 62 died (fatal group) and 57 survived (survival group) within 28 days of disease onset. The genotypes of these individuals were detected using TaqMan allelic discrimination assays, and its correlations with susceptibility and outcome of sepsis were analyzed. There was no significant difference in genotype frequencies and allelic frequencies of TRPM2 SNP rs1556314 between septic patients and the controls (all >0.05). And no significant difference in genotype frequencies and allelic frequencies of TRPM2 SNP rs1556314 was observed between the survivors and fatal cases of septic patients (all >0.05). The TRPM2 SNP rs1556314 does not have significant